Neurobiological links between depression and AD: The role of TGF-β1 signaling as a new pharmacological target. (April 2018) - Caraci, Filippo; Spampinato, Simona Federica; Morgese, Maria Grazia; Tascedda, Fabio; Salluzzo, Maria Grazia; Giambirtone, Maria Concetta; Caruso, Giuseppe; Munafò, Antonio; Torrisi, Sebastiano Alfio; Leggio, Gian Marco; Trabace, Luigia; Nicoletti, Ferdinando; et al.
Graphical abstract: Abstract: In the last several years a large number of studies have demonstrated the neurobiological and clinical continuum between depression and Alzheimer's disease (AD). Depression is a risk factor for the development of AD, and the presence of depressive symptoms significantly increases the conversion of Mild Cognitive Impairment (MCI) into AD. Common pathophysiological events have been identified in depression and AD, including neuroinflammation with an aberrant Tumor Necrosis Factor-α (TNF-α) signaling, and an impairment of Brain-Derived Neurotrophic Factor (BDNF) and Transforming-Growth-Factor-β1 (TGF-β1) signaling. TGF-β1 is an anti-inflammatory cytokine that exerts neuroprotective effects against amyloid-β (Aβ)-induced neurodegeneration, and it has a key role in memory formation and synaptic plasticity. TGF-β1 plasma levels are reduced in major depressed patients (MDD), correlate with depression severity, and significantly contribute to treatment resistance in MDD. The deficit of Smad-dependent TGF-β1 signaling is also an early event in AD pathogenesis, which contributes to inflammaging and cognitive decline in AD. A long-term treatment with antidepressants such as selective-serotonin-reuptake inhibitors (SSRIs) is known to reduce the risk of AD in patients with depression and, SSRIs, such as fluoxetine, increase the release of TGF-β1 from astrocytes and exert relevant neuroprotective effects in experimental models of AD. We propose the TGF-β1 signaling pathway as a common pharmacological target in depression and AD, and discuss the potential rescue of TGF-β1 signaling by antidepressants as a way to prevent the transition from depression to AD.